Konsep Kepribadian Matang dalam Budaya Jawa-Islam: Menjawab Tantangan Globalisasi - Nita Trimulyaningsih (Faculty of Psychology Universitas Gadjah Mada, 2017)
Globalization that brings issues of equality and freedom further obscures the personal identity of Javanese. This can lead to the absence of coherence in the individuals that inhibits maturity and bring up negative experiences such as anxiety, depression, and confusion. In Javanese society, there are criteria of personal maturity. Based on the literature review, these characteristics include the existence of appreciation to God, the effort to maintain internal and external harmony, emphasis on roso, and the existence of awareness and control. These characteristics need to be maintained in Javanese to achieve maturity, either individually or integrated into the context of education, psychotherapy, leadership, and social change. This process of internalization and actualization of value is important as a part of a culture that has been tested for thousands of years as a guardian of the harmony, and also that it is relevant, important and capable of being applied in the era of globalization.